2012
DOI: 10.1128/jcm.00676-12
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Valve Endocarditis Due to Neisseria skkuensis, a Novel Neisseria Species

Abstract: eWe describe the first reported case of endocarditis due to Neisseria skkuensis. The organism from the blood cultures taken on admission day was identified initially as unidentified Gram-negative cocci by Vitek2. Finally, it was identified as Neisseria skkuensis by 16 rRNA gene sequence analysis. CASE REPORTA 41-year-old man was admitted to our hospital with a 1-week history of febrile sense, chills, sweating, aggravation of dyspnea, and hypotension during hemodialysis. He had a complicated history, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In clinical point of view, previous studies showed that N. skkuensis would be an important pathogen in immunocompromised patients. Our patient had liver cirrhosis and hepatic cellular carcinoma, similar with the case of Park et al [8] which had liver cirrhosis and chronic kidney disease, other than diabetes mellitus. It is certain that this novel species is an important opportunistic pathogen in patients with underlying diseases such as diabetes mellitus and liver cirrhosis.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In clinical point of view, previous studies showed that N. skkuensis would be an important pathogen in immunocompromised patients. Our patient had liver cirrhosis and hepatic cellular carcinoma, similar with the case of Park et al [8] which had liver cirrhosis and chronic kidney disease, other than diabetes mellitus. It is certain that this novel species is an important opportunistic pathogen in patients with underlying diseases such as diabetes mellitus and liver cirrhosis.…”
Section: Discussionsupporting
confidence: 68%
“…Previous reports described N. skkuensis infections in diabetic foot ulcer and endocarditis with underlying disorders such as diabetes and liver cirrhosis, respectively [7][8][9]. We report the first case of cellulitis due to N. skkuensis in the patient with liver cirrhosis and hepatic cellular carcinoma who was diagnosed incidentally.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Notably, although Neisseria polysaccharea is the most evolutionarily related species to N. meningitidis and N. gonorrhoeae (Bennett et al, 2013;Bennett et al, 2014), there are far fewer case reports for disease caused by this species compared with N. lactamica and N. cinerea. Visceral botryomycosis: 20-year-old male with chronic granulomatous disease Washburn et al (1985) N. sicca Endocarditis: 17 cases mostly associated with mitral valve replacement Sommerstein et al (2013) Meningitis: 44-year-old female following intracranial haemorrhage and ventriculostomy tube placement Carter et al (2007) Conjunctivitis: 79-year-old female with no history of trauma or surgery Eser et al (2014) N. skkuensis Fever and foot ulcer: 50-year-old male with type 2 diabetes, suffering from complications Lee et al (2010) Prosthetic valve endocarditis: 41-year-old male with liver cirrhosis, chronic kidney disease, 1 year after a mechanical mitral valve replacement due to endocarditis caused by MRSA Park et al (2012) N. cinerea Peritonitis: 38-year-old male with type 2 diabetes, 2 years after end-stage renal disease and CAPD Taegtmeyer et al (2006) Neonatal conjunctivitis: new born, from mother during birth Bourbeau et al (1990) Bacteraemia: 47-year-old male, underlying ethanol abuse and polymicrobial sepsis Southern & Kutscher (1987) Commensal Neisseria Some Neisseria species have been reported to be bona fide animal pathogens (Table 2). In mammals, N. animaloris (EF-4a) and N. zoodegmatis (EF-4b) cause disease in animals within the Felidae family, including more than ten cases of disease in cats (Baral et al, 2007;Corboz et al, 1993;McParland et al, 1982), two Chinese leopards, a lion and a tiger cub (Fenwick et al, 1983;Lloyd & Allen, 1980;Perry & Schlingman, 1988).…”
Section: Disease Associated With Commensal Neisseriamentioning
confidence: 99%